2018
DOI: 10.1108/jaoc-03-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of accrual accounting by Malaysian federal government

Abstract: Purpose The purpose of this paper is to examine factors influencing the readiness of public sector accountants to implement the accrual accounting system in the Malaysian Federal Government. The readiness was measured in terms change commitment and change efficacy. Design/methodology/approach The study uses a questionnaire survey that comprises three factors (change valence, task knowledge and task availability) in predicting readiness to implement the accrual accounting system. Multiple regressions were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 28 publications
5
55
0
4
Order By: Relevance
“…Based on the research conducted by Phillips (2017), he found that change valence has a significant positive impact on organisational readiness for changes in software which includes change commitment. A similar result was found by Ismail et al (2018) who conducted a study on accountants' readiness for accrual accounting adoption. They found that change valence is positively significant in affecting change commitment.…”
Section: Literature Reviewsupporting
confidence: 81%
See 3 more Smart Citations
“…Based on the research conducted by Phillips (2017), he found that change valence has a significant positive impact on organisational readiness for changes in software which includes change commitment. A similar result was found by Ismail et al (2018) who conducted a study on accountants' readiness for accrual accounting adoption. They found that change valence is positively significant in affecting change commitment.…”
Section: Literature Reviewsupporting
confidence: 81%
“…Accrual accounting is an accounting basis which records economic events that can reflect an entity's financial position and performance regardless of when the cash transactions occur (Ismail, Siraj, & Baharim, 2018;Khan & Mayes, 2009). Accrual accounting exists as an alternative in financial reporting preparation due to the weaknesses noted in cash accounting.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, human resources capability and information technology were found to be important factors by [28], [2] and [45] to raise the readiness of government financial personnel in the context of Indonesia, Malaysia and Thailand respectively. Additional important factors associated with readiness of financial personnel in the migration process such as change valence, task knowledge and task availability were found by [29] study in Malaysia. However, none of the abovementioned studies addressed the role of psychological needs (i.e.…”
Section: Factors Influencing the Readiness Of Government Financial Pementioning
confidence: 83%